Characterization of the airway microbiome in preterm infants with bronchopulmonary dysplasia - Bao, Zhidan; Niu, Limei; Ma, Yizhe; Deng, Xianhui; Wang, Luchun; Tao, Mingyan; Yu, Renqiang (Frontiers in Cellular and Infection Microbiology, 2025)
Background and aimsBronchopulmonary dysplasia (BPD) represents a persistent respiratory condition that primarily affects preterm infants, distinguished by abnormal lung development and function. Previous studies have indicated a significant association between the pulmonary microbiome and various respiratory diseases. This study aimed to compare the airway microbiome composition and its temporal changes in preterm infants with and without BPD.MethodsWe conducted a cohort study involving 14 infants diagnosed with BPD and 10 preterm infants without BPD, all born at a gestational age (GA) < 32 weeks. Tracheal aspirates were collected on day 1 during intubation, as well as on days 7 and 14 following the intubation procedure. Subsequently, bacterial DNA was extracted, and the 16S rRNA genes were amplified and sequenced to characterize the airway microbiome.ResultsThe demographic and clinical features, such as gestational age, birth weight, and sex ratio, were similar across the groups. However, BPD infants required prolonged duration for Continuous Positive Airway Pressure (25.0 d vs 8.5 d, P = 0.001), oxygen therapy (38.0 d vs 20.5 d, P = 0.001), antibiotic treatment (9.5 d vs 4.5 d, P = 0.004), and prolonged hospital admissions (44.0 d vs 25.5 d, P = 0.002). Microbiome analysis revealed that the BPD infants exhibited reduced bacterial diversity at birth and a consistent pattern of diminished bacterial diversity over time compared to the non-BPD group, as indicated by a lower Shannon index. The BPD group also showed a distinct microbial community composition, with significant differences in β-diversity observed at day 14 post-incubation. At the phylum level, both groups exhibited an increase in Firmicutes in the first two weeks, while the BPD group showed a progressive decline in the relative abundance of Bacteroidetes. At the genus level, the BPD infants exhibited an increased proportion of Streptococcus and Acinetobacter, and a decreased abundance of Prevotella over time.ConclusionsThese findings indicate that the airway microbiome in infants with BPD is characterized by reduced diversity and distinct microbial profiles, which may contribute to the pathogenesis of the disease. Understanding these microbiome dynamics may help develop targeted therapeutic strategies aimed at modulating the microbiome to prevent or mitigate BPD in preterm infants.